Dampak Shopping Lifestyle, Price Discount, Self Control Terhadap Impulse Buying Generasi Z pengguna Tokopedia - Fitriah, Ridhatul; Mas Oetarjo; Alshaf Pebrianggara (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
E-commerce makes it easier for people to carry out buying and selling transactions without having to expend energy so that people prefer to shop online because of the practicality that e-commerce provides. This situation provides changes in consumer behavior where people prioritize desires over needs when shopping. Tokopedia, one of the e- commerce sites, is here to provide updates for the public in carrying out shopping transactions. This encourages researchers to examine what variables influence impulse buying. The aim of this research is to find out what variables influence the impulse buying behavior of Tokopedia users. This research uses quantitative methods with primary data types. Respondents in this study were determined using the Lemeshow formula and there were 100 respondents. Testing of this research data uses multiple linear regression analysis, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, coefficient of determination test and T test. The results of this study show that the three variables, namely shopping lifestyle, price discount and self control have a significant effect on the impulse buying of Tokopedia users